Diurnal Characteristics and Long-Term Changes in Extreme Precipitation in the Republic of Korea - Do-Hyun Kim; Jin-Uk Kim; Jaekwan Shim; Chu-Yong Chung; Kyung-On Boo; Sungbo Shim (Atmosphere, 2025)
In this study, diurnal characteristics and long-term changes in extreme precipitation (PR) in the Republic of Korea (KR) are investigated. Hourly PR data from 59 ASOS stations across the country over a 50-year period (1973–2022) are used. The focus is on the summer season (June to September), during which extreme PR frequently occurs. During the period 1973–1997 (FP), both the amount and frequency of extreme PR events peak between 01 and 09 LST. In contrast, during the period 1998–2022 (LP), a notable increase in extreme PR and its frequency is observed between 04 and 12 LST, with the peak occurrence hours shifting to this time frame. An analysis of atmospheric variables related to extreme PR is conducted for the 04–12 LST time frame. Compared to all PR events during the summer season, a low-level low-pressure anomaly is found west of the KR, leading to southerly winds and positive specific humidity anomalies over the south of the KR. Relative to the FP period, both the amplitude and frequency of high water vapor content have increased during the LP period. This intensified moisture may be associated with the observed increase in extreme PR during 04–12 LST. However, no significant changes are found in the strength and frequency of the southerly wind.